The value of the dynamics some interleukins of blood serum in patients with multiresystance relapse pulmonary tuberculosis - Butov, D (Annals of Mechnikov's Institute, 2020)
The study of interleukin (IL)-2, IL-4 and IL-8 in 140 patients with pulmonary tuberculosis and 30 healthy donors. In patients with pulmonary tuberculosis before treatment was an increase levels of IL-2, IL-8 and decrease IL-4 compared to the relatively healthy donors. After two-month standard antimycobacterial therapy found significant decrease IL-2, IL-8 and increase IL-4 in patients with pulmonary tuberculosis. More significant changes were expressed as before treatment so after two months of chemotherapy were observed in patients with pulmonary multirezystent pulmonary tuberculosis, especially in patients with recurrent process than patients without the multirezystent pulmonary tuberculosis and newly diagnosed pulmonary tuberculosis.